2022
DOI: 10.1002/ejp.2021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of co‐crystal of tramadol‐celecoxib (CTC) in acute moderate‐to‐severe pain after abdominal hysterectomy: A randomized, double‐blind, phase 3 trial (STARDOM2)

Abstract: Background: STARDOM2 is a randomized, double-blind, phase 3 trial evaluating the efficacy and safety of co-crystal of tramadol-celecoxib (CTC)-a firstin-class analgesic co-crystal comprising racemic tramadol hydrochloride and celecoxib in a supramolecular network that modifies their pharmacokinetic properties-for the management of acute postoperative pain (NCT03062644;EudraCT:2016-000593-38).Methods: Patients with moderate-to-severe pain following abdominal hysterectomy were randomized 2:2:2:2:2:1 to oral CTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Phase I clinical studies confirmed that the co-crystal was associated with the expected improved pharmacokinetic profile relative to either of the individual formulations or their combination [150]. Subsequently, Phase II and III studies confirmed the significant improvement in the risk/benefit ratio observed with the co-crystal relative to either agent alone [151][152][153]. Seglentis ® is now approved for the treatment of acute pain in adults that is severe enough to require an opioid analgesic for which other treatments are inadequate [154].…”
Section: Pharmacological Treatment Of Chronic Np: Co-crystallizationmentioning
confidence: 75%
“…Phase I clinical studies confirmed that the co-crystal was associated with the expected improved pharmacokinetic profile relative to either of the individual formulations or their combination [150]. Subsequently, Phase II and III studies confirmed the significant improvement in the risk/benefit ratio observed with the co-crystal relative to either agent alone [151][152][153]. Seglentis ® is now approved for the treatment of acute pain in adults that is severe enough to require an opioid analgesic for which other treatments are inadequate [154].…”
Section: Pharmacological Treatment Of Chronic Np: Co-crystallizationmentioning
confidence: 75%
“…Although celecoxib monotherapy is not approved for use in acute pain in Europe, it is approved for this indication in other geographic regions. A recent phase 3 trial—of postoperative pain following abdominal hysterectomy—included both tramadol and celecoxib comparator arms and found CTC 200 mg to be noninferior, but not superior, to tramadol [ 29 ]. Another recent phase 3 trial of CTC 200 mg after bunionectomy with osteotomy [ 28 ] included a celecoxib comparator arm (100 mg BID) and demonstrated that CTC significantly improved efficacy over celecoxib, as well as over tramadol.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 3 trial of pain following bunionectomy with osteotomy, CTC was associated with greater pain relief than similar daily doses of tramadol or celecoxib, with comparable tolerability as tramadol [ 28 ]. CTC 200 mg was also found to be noninferior and to have an improved benefit/risk profile compared with tramadol in a phase 3 trial of pain following abdominal hysterectomy [ 29 ]. CTC was approved by the US Food and Drug Administration in 2021 [ 30 ], and received its first European regulatory approval (in Spain) in September 2023 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Інтенсивність болю після гістеректомії була нижчою в разі комбінованого використання трамадолу із целекоксибом, ніж трамадолу окремо [21]. Додавання налбуфіну як допоміжного препарату для інтратекального введення до бупівакаїну при проведенні нейроаксіальної анестезії покращувало якість і тривалість сенсорної блокади та подовжувало післяопераційну аналгезію.…”
Section: огляд літературиunclassified